Feasibility Study of Win-In-Ground for Rescue Operation in Kepulauan Riau - Prayetno, E.; Koto, Jaswar; Kader, A.S.A. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2013)
This study aims to investigate performance of current rescue facilities and position based on statistic data of sea accident between 2010 and 2011 in Kepulauan Riau. Current rescue facilities are located at the latitude 0.93105 and longitude 104.4. Using the statistic data, an optimal recue location and facilities in Kepulauan Riau are determine based on International Maritime Organization (IMO) standard. International Maritime Organization requirement , a n emergency, passengers should be able to leave the ship with time 60 minutes. The optimal position and rescue facilities are determined using Great Circle Distance- Spherical Trigonometry and Statistical of Standard Error methods. In this study, simulation code is developed using visual basic 2010 language. Results of simulation show current rescue facility requires a lot of time to reach the accident location which is up to 12.5 hours. In order to meet IMO requirement, this study proposes wing in ground for rescue operation. Using current rescue location, wing in ground also does not meet the IMO standard which is up to 3.04 hours. Additional, this study divides the Kepulauan Riau into two regions of rescue operation. The optimal for rescue facilities of region 1, at the latitude 0.74568 and longitude 104.36256 , and based on the distribution of the accidents in Kepulauan Riau 2010-2011, current rescue facility required up to 5.6 hours to reach the accident area, while the wing in ground facilities required up to 1.3 hours. The optimal for rescue facilities of region 2, at the latitude 3.00338 and longitude 107.79373 , current rescue facility required up to 5 hours to reach the accident area, while the wing in ground facilities required shorter time that is up to 1.2 hour.